Role of gallium 67 thoracic scintigraphy in the diagnosis and staging of patients suspected of bronchial carcinoma. - Pannier, R (1982)
Gallium 67 (67Ga) lung scanning was performed in 100 consecutive cases in which because of the history, clinical data, or abnormal radiological findings, a bronchial carcinoma was suspected. This study allows the conclusion that a negative as well as a positive scan is an important element in the diagnosis of some cases of bronchial carcinoma. The method is most helpful in the preoperative diagnosis of circumscribed peripheral shadows and in the assessment of suspected hilar enlargement; it may even visualise hidden malignant tumours. Gallium 67 scanning is also valuable in the assessment of hilar and mediastinal involvement in the presence of a proven primary lung tumour. This study supports the view that in the presence of a negative mediastinal scan the patient may be spared mediastinoscopy and be referred directly for operation.